Hubungan Power Lengan dan Fleksibilitas Punggung dengan Hasil Lemparan Three Point Bola Basket - Permana, Regi; Kurniawan, Asep Ridwan; Marwoto, Toto; Sudrazat, Adang (Jurnal Keolahragaan, 2023)
This study used a correlation method using test and measurement techniques on independent variables, namely leg power, and back flexibility, and bound variables, namely three-point shot throws. The population used was SMA Negeri 3 Kabupaten Ciamis The sample used amounted to 22 people who participated in extracurricular basketball. Based on the results of the regression line linearity test shows that the number obtained is greater than 0.05, it is proven for the independent variable arm power with a three-point shoot is 0.276 > 0.05, and for back muscle flexibility with a three-point shoot is 0.409 > 0.05. It can be said that the data is linear. Based on the data, the correlation test results show that in the sig column. F change yields the number 0.383. This means that if the value obtained is greater than 0.05 then there is no correlation or in other words unrelated. According to the results of the study, "There is no relationship between arm power and back muscle flexibility with a three-point shoot in students of SMA Negeri 3 Ciamis Regency.